Sources, Load, Vertical Distribution, and Fate of Wintertime Aerosols North of Svalbard From Combined V4 CALIOP Data, Ground‐Based IAOOS Lidar Observations and Trajectory Analysis. Issue 2 (30th January 2018) - Di Biagio, C.; Pelon, J.; Ancellet, G.; Bazureau, A.; Mariage, V.
Abstract: We have analyzed aerosol properties at the regional scale over high Arctic north of Svalbard between October 2014 and June 2015 from version 4 (V4) CALIOP (Cloud and Aerosol Lidar with Orthogonal Polarization) spaceborne observations and compared results with surface lidar observations from IAOOS (Ice‐Atmosphere‐Ocean Observing System) platforms. CALIOP data indicate a maximum in aerosol occurrence at the end of winter attributed to low‐level (0–2 km) and midtropospheric (2–5 km) particles identified in CALIOP V4 product as being mostly of dust origin. Another maximum was observed in October–December attributed to clean marine particles below 2 km and smoke and dust above. The 532 nm aerosol extinction was in the range 1–8 Mm −1 (0–2 km), 1–18 Mm −1 (2–5 km), and 0–6 Mm −1 (5–10 km), a factor 2 lower compared to values previously reported using CALIOP V3 data set. Aerosols are identified from trajectory analyses to originate mostly from Russia/Europe at all altitudes, and also North America above 2 km, and it is concluded that dust and clean marine types are most probably overrepresented in the analyzed CALIOP data set. It is proposed that most part of dust types are diamond dust, while part of clean marine are polluted species, as corroborated from colocated polarized lidar IAOOS observations. IAOOS observations allowed confirming the identified sensitivity of CALIOP with a particle backscatter coefficient of ~0.001 km −1  sr −1 at 532 nm. For optically thicker layers CALIOP is shown to be a valuable tool to follow transport of aerosol layers in the Arctic and identify their possible modifications. Key Points: Combining CALIOP satellite and IAOOS local‐scale lidar observations allows to better characterize properties and transport of Arctic aerosol Dust‐type aerosols are overrepresented in CALIOP Arctic data set, and a large part of it is most probably corresponding to diamond dust The V4 CALIOP 532 nm aerosol extinction is a factor 2 lower than averages reported by Di Pierro et al. (2013 ) using V3 data set